A qualitative study of parental involvement in Yamaha Junior Music Course (JMC) at Kota Damansara, Selangor / Choo Yi Jia - Choo, Yi Jia (2017)
This research is a case study that examined parents’ involvement in Yamaha Junior Music Course (JMC) where parental engagement is compulsory as part of the course syllabus. The requirement of parent accompaniment conforms to findings from past literature that reveal parental involvement led to positive outcome in students’ achievement in formal education. However, there is a lack of research into parents’ roles during such music classes like JMC and at the same time, a clear guidelines regarding parental involvement is missing in the JMC syllabus, this becomes the aim of the present research. A qualitative research framework was selected in the context of this study in order to examine parent perception and their behaviour during the class. Data were collected through open-ended interviews, observations, and participation. Patterns of parents’ behaviour, involvement, and their perceptions are analysed in this research. The outcome reveals perception and patterns of behaviour that may furnish new knowledge to the various stakeholders involved in the JMC.